الاسم بين الارتجال والنقل :‏ ‏دراسة لغوية تأصيلية /‏ - حويطي، محمد بن سعيد بن عطية (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2011)
This study examines two systems of nouns of languages: improvised and transfer, and etymologizes them, because they help in the development, survival and continuity. They are studied so that we understand the benefits and lesser the negatives impacts based on the intellectual dispute between linguists and scholars of Islamic study. The different viewpoints among them on improvised and transferred nouns allowed the system to be studied in tow different methods. It is difficult to find an accurate and comprehensive code to recognize these systems, their mechanism, and the linguistics structures. This study requires tracking these systems by collecting data, analyzing and identifying the relationships that govern them, and drawing the mechanisms for their work, to present a comprehensive concept that describes the systems accurately. This is necessary in order to guarantee access to subjective results, knowing the origin of each system and definitions, and monitoring their methods, types, causes, and conditions, and their relationship with other linguistic phenomena. The main findings of the study suggest that there is a need to develop a mechanism to examine each noun to determine whether it is improvised, and to determine how the general framework depict both of them as linguistic systems, and to explain when the cases of improvised noun are triplicate rather than transferred, and to prove that improvisation and transferred systems represent the accuracy of all the constant changes in, first, the generative structures, and rhythm, and second, in generative semantics, and finally to prove that improvised and transferred nouns represent the dualism of origin and branch, whereby the first is origin, the second is branch. The study tries to identify the similarities in other languages that contain regular improvised and transferred nouns, and suggest general rules that can be applied to these languages.